Phylogeographic analysis reveals an ancient East African origin of human herpes simplex virus 2 dispersal out-of-Africa - (:unkn) unknown (My University, 2022)
Human herpes simplex virus 2 (HSV-2) is a ubiquitous, slowly evolving DNA virus. HSV-2 has two primary lineages, one found in West and Central Africa and the other found worldwide. Competing hypotheses have been proposed to explain how HSV-2 migrated out-of-Africa (i)HSV-2 followed human migration out-of-Africa 50-100 thousand years ago, or (ii)HSV-2 migrated via the transAtlantic slave trade 150-500 years ago. Limited geographic sampling and lack of molecular clock signal has precluded robust comparison. Here, we analyze newly sequenced HSV-2 genomes from Africa to resolve geography and timing of divergence events within HSV-2. Phylogeographic analysis consistently places the ancestor of worldwide dispersal in East Africa, though molecular clock is too slow to be detected using available data. Rates 4.2 × 10 −8 −5.6 × 10 −8 substitutions/site/year, consistent with previous age estimates, suggest a worldwide dispersal 22-29 thousand years ago. Thus, HSV-2 likely migrated with humans from East Africa and dispersed after the Last Glacial Maximum.
Keywords: African Research